Peningkatan Aktivitas Belajar Peserta Didik pada Materi Pola Hereditas Mata Pelajaran Biologi dengan Menerapkan Model Problem Based Learning di Kelas XII IPS SMA Muhammadiyah I Malang - Mifta, Nur Aulia Miftahul Jannah (Jurnal Pendidikan Biologi Undiksha, 2023)
Learning activities are very important in learning. Learning will be successful if students are actively involved in learning, so we need a learning model that can enhance learning activities. This classroom action research aims to increase students' learning activities through the application of the Problem Based Learning (PBL) learning model. This research was conducted for two cycles by applying three stages of lesson study namely plan, do, and see. The research participants were class XII students at a high school in Malang City, consisting of 10 students. Data collection was obtained by class observation. The treatment in this study is the application of the PBL model in learning. The dependent variable in the study is learning activity which is measured based on the proportion of learning activities carried out by students. The research results show that the application of the PBL model. The research results in each learning cycle obtained the proportion of learning activities in the first cycle of 55% and second cycle of 83%. Research shows that the PBL model is effective for increasing learning activities in students. This study also emphasizes the importance of student learning activities during learning.